STRATEGIC PARTNERSHIP EUROPEAN UNION - BRAZIL: 10 YEARS OF COMMON PRIORITIES - de França., Nathalia Penha Cardoso (Revista de Direito Internacional e Globalização Econômica, 2017)
More than five decades mark the relations between Brazil and the European Union. The last EU-Brazil Summit, held in Brussels, 2014, reaffirmed the Joint Action Plan carved in Rio de Janeiro, 2002, by repeating the three large areas of cooperation: Economic growth, job creation and competitiveness; Foreign Policy; and Tackling Global Challenges. In the document, is was also agreed to strengthen the bilateral political dialogue in order to converge further on the global agenda and on both parties positions in international fora. Both parties restated the importance of a strong and effective multilateral UN system, based upon international law. This article aims to give an overview of the EU-Brazil relations, especially mentioning Brazil as a recognized emerging power, its role in Latin America and the shared commitment to multilateralism. On a second moment, the text will analyse all the EU-Brazil Summits since 2007, emphasising The Strategic Partnership forged in the occasion on the 1st Summit and more elaborated on the 2nd. At the end, it is found a brief opinion on the impact on EU-Mercosur relations, permeating the connections Brazil-Mercosur and EU-Mercosur.